If cos-1 x - cos-1 y/2 = ​alpha, then 4x2 - 4xy cos alpha + y2 = ?
(a) 4 (b) 2sin2 alpha
(c) -4sin2 alpha (d) 4sin2 alpha

We have,   cos-1x - cos-1y2 = αcos-1xy2 + 1-x21-y24 = αxy2 + 1-x21-y24 = cos αxy2 + 4-y2-4x2+x2y22 = cos αxy + 4-y2-4x2+x2y22 = cos αxy + 4-y2-4x2+x2y2 = 2 cos α 4-y2-4x2+x2y2 = 2 cos α - xy4-y2-4x2+x2y2 = 4 cos2α + x2y2 - 4xy cos α4-y2-4x2 = 4 cos2α - 4 xy cos α4x2 + y2 - 4xy cos α = 4 - 4 cos2α4x2 + y2 - 4xy cos α = 41-cos2α4x2 + y2 - 4xy cos α = 4 sin2α

  • 62
What are you looking for?